Definite Integration

Calculus Level 5

0 e ( x 2 + 4 x 2 ) d x = ? \displaystyle \int _{ 0 }^{ \infty }{ { e }^{ -({ x }^{ 2 }+4x^{ -2 }) } } \ dx = \ ?

Details and Assumptions

  • Does not require any advanced skills like gamma function.
  • Not an original, But I felt it is a nice problem


The answer is 0.01623.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Mvs Saketh
Mar 2, 2015

I will give a hint only, if someone requires the answer, then comment

Let the integral be 'I' replace '2' with a varriable 'a' now put a/x = z

differentiate 'I' with respect to 'a',

and you will know where to go next :)

I = 0 e ( x 2 + 4 x 2 ) d x \displaystyle I=\int _{ 0 }^{ \infty }{ { e }^{ -({ x }^{ 2 }+\frac { 4 }{ { x }^{ 2 } } ) }dx }

x = 2 t x=\frac{2}{t}

I = 0 2 t 2 e ( t 2 + 4 t 2 ) d t = 0 2 x 2 e ( x 2 + 4 x 2 ) d x \displaystyle I = \int _{ 0 }^{ \infty }{ { \frac { 2 }{ { t }^{ 2 } } e }^{ -({ t }^{ 2 }+\frac { 4 }{ { t }^{ 2 } } ) }dt } =\int _{ 0 }^{ \infty }{ { \frac { 2 }{ { x }^{ 2 } } e }^{ -({ x }^{ 2 }+\frac { 4 }{ { x }^{ 2 } } ) }dx }

2 I = 0 ( 1 + 2 x 2 ) e ( x 2 + 4 x 2 ) d x = 0 ( 1 + 2 x 2 ) e ( ( x 2 x ) 2 + 4 ) d x \displaystyle 2I=\int _{ 0 }^{ \infty }{ ({ 1+\frac { 2 }{ { x }^{ 2 } } )e }^{ -({ x }^{ 2 }+\frac { 4 }{ { x }^{ 2 } } ) }dx }=\int _{ 0 }^{ \infty }{ ({ 1+\frac { 2 }{ { x }^{ 2 } } )e }^{ -{ (({ x }-\frac { 2 }{ { x } } ) }^{ 2 }+4) }dx }

x 2 x = y x-\frac{2}{x} = y

2 I = e ( y 2 + 4 ) d y = e 4 e y 2 d y \displaystyle 2I=\int _{-\infty }^{ \infty }{ { e }^{ -{ (y }^{ 2 }+4) }dy } ={ e }^{ -4 }\int _{ -\infty }^{ \infty }{ { e }^{ -{ y }^{ 2 } }dy }

integral is a standard gaussian integral

2 I = e 4 π 2I={ e }^{ -4}{ \sqrt{\pi} }

I = π 2 e 4 \displaystyle I=\frac { \sqrt { \pi } }{ 2{ e }^{ 4 } }

U Z - 6 years, 3 months ago

Log in to reply

Nice, Theres another way it can be done without using gaussian integral as well, i shall tag you after posting solution

Mvs Saketh - 6 years, 3 months ago

Log in to reply

@Mvs Saketh can u post the solution to this problem Thanks

Deena Albert - 6 years, 3 months ago

@Mvs Saketh No there isn't. Even if we take your method of differentiating the integral we would get a differential equation in terms of a as I'(a) =-2I(a). Solving it we would have I ( a ) = C e 2 a I(a) = Ce^{-2a} To evaluate the constant C you would have to put a=0 and thereby you would arrive at the gaussian integral and the constant C C would evaluate to nothing but π 2 \frac{\sqrt{\pi}}{2} . So in anyways whether you do it by @U Z method or by your method you would need the gaussian integral at some step or the other.

Arghyadeep Chatterjee - 1 year, 4 months ago

a small coorection required

it should be x 2 x = y x-\frac{2}{x}=y

Tanishq Varshney - 6 years, 3 months ago

Log in to reply

Thanks what was your method?

U Z - 6 years, 3 months ago

Log in to reply

@U Z I applied the same method.

Tanishq Varshney - 6 years, 3 months ago

what are gaussian integral?

Deena Albert - 6 years, 3 months ago

Log in to reply

the integral of e x 2 e^{-x^2} over entire line is π \sqrt{\pi} . It is used for statistics, analysis and advanced calculus

Figel Ilham - 6 years, 3 months ago

Log in to reply

@Figel Ilham Sorry, but I think you made a mistake , it should be e^{-x^{2}} to get e x 2 \huge e^{-x^{2}}

A Former Brilliant Member - 6 years, 3 months ago

Log in to reply

@A Former Brilliant Member Oh yeah. I use the brackets instead the curly one. I'll fix it.. Thanks for reminding me

Figel Ilham - 6 years, 3 months ago

HI ,I think this might be of interest to you :)

A Former Brilliant Member - 6 years, 3 months ago

I think that I did correct in waiting for this problem to get rated !!

A Former Brilliant Member - 6 years, 3 months ago

Log in to reply

thank you for the information

Deena Albert - 6 years, 3 months ago

PLZ POST UR SOLNNNNN

rajat kharbanda - 6 years, 1 month ago
Prakhar Bindal
Sep 27, 2016

Firstly let x = t*root(2)

Then replace t by 1/t and add the two integrals

Now substitute t-1/t = y and taking somethings common you will get the pretty standard gaussian integral!

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...